THE CONCEPT OF MAḤABBAH PERSPECTIVE OF RABI'ATUL ADAWIYAH - Humdan, Siti Asiah (STAI Darul Kamal NW Kembang Kerang, 2020)
The Divine love story of Rabi’atul Adawiyah is one of the legendary stories that has been told from time to time. This story has washed away many hearts of listeners, especially those who want to be one with God. However, this story is often only used as a fairy tale that leaves no mark on the listeners, even though this story gives a great awareness of the importance of one's love for others and of course for God. Rabiatul Adawiyah appeared as a tough woman not necessarily a great lover, but was born from the womb of a life full of struggles. His life experiences, socio-political conditions, his views on world life, and the existence of his God became a long process in his search for and discovering the concept of divine love.